만성 C형간염 환자에게 페그인터페론과 리바비린 병합치료 중 피부에 발생한 혈관염 1예 - 김연호; Youn Ho Kim; 한우식; Woo Sik Han; 이순재; Sun Jae Lee; 오성남; Sung Nam Oh; 최도원; Do Won Choi; 변관수; Kwan Soo byun; et al. (Clinical and molecular hepatology, 2007)
본 사례와 같이 만성 C형간염 환자에서 PEG- IFN 치료 중 발생한 혈관염은 임상적으로 해결하기 어려운 문제가 될 수 있다. 그러므로 향후 PEG- IFN 치료 중 발생한 부작용들을 분석하고, 부작용의 발생과 관련된 병리 요인을 분석할 필요가 있다. There has been an increase in the number of patients treated with pegylated interferon (PEG-IFN) and ribavirin due to the better antiviral efficacy. The main serious adverse events of PEG-IFN plus ribavirin combination therapy are bone marrow suppression and hemolytic anemia. However, there are few reports of vasculitis occurring during PEG-IFN therapy. We describe a patient who developed vasculitis during the treatment of chronic hepatitis C with PEG-IFN and ribavirin. (Korean J Hepatol 2007;13:419-422) KCI Citation Count: 0